Studi Retrospektif: Transformasi Moral Dewasa melalui Pendidikan Etika Kristen di Sekolah Minggu - Silaen, Riste Tioma; Zega, Yanuar Ada (Sekolah Tinggi Teologi Tenggarong, 2025)
In the increasingly digitalized era that dominates human life, there has been a significant shift in moral values among young adults. This phenomenon necessitates a thorough investigation into the moral transformation occurring, particularly through Christian ethical education in Sunday school. The primary issue in this research is the lack of understanding regarding how Christian ethical education in Sunday school influences ethical decision-making and the formation of individual morality in adulthood. This research is essential as it provides deep insights into the relevance of Christian ethical education within the context of everyday life. The study aims to explore the role of Christian ethical education in moral transformation during adulthood through a retrospective study of individual experiences. The research employs a descriptive qualitative method with a retrospective approach, including article analysis and literature review. The findings indicate a positive correlation between Christian ethical education in childhood and moral consistency in adulthood. In conclusion, Christian ethical education in Sunday school has a significant impact on shaping long-term morality. This research offers a new perspective in the study of religious and ethical education.